EducAção em Rede JC: metodologia para formação continuada de professores no uso das TIC - Botton, Alessandra Ferigollo (2017)
This study resulted in the production, experimentation and analysis of the use of a didactic-methodological proposal for the continuous training of teachers in the use of ICT. The proposal was constituted by the product of this research: JC EducAction Network, a Virtual Environment developed through the Moodle (Modular Object-Oriented Dynamic Learning Environment) platform. The guiding methodology of this study is action research, which aims to provide training that allowed the participants not only to improve their knowledge regarding the handling of technologies, but also to feel empowered and encouraged to insert them to their pedagogical practices. In this way, JC EducAction Network was organized and structured in workshops. The training course was offered in a semipresencial environment and was intended for teachers of the Municipal Elementary Education School Élio Salles, in the city of Júlio de Castilhos/RS. The product was evaluated by the data collected through the registration of the researcher's observations, research questionnaires and discussion forums. After analyzing the collected data, it could be oberved that the professional development was related to the real needs of improvement and they provided the empowerment of the teachers to plan and integrate the ICT to their pedagogical practices and to create their own didactic materials. As for JC EducAction Network, it presented itself as a playful, pleasant, and well-organized space, and because of its didactic structure, it provided the autonomy and motivation of the participants, as well as a space for sharing experiences and knowledge about the integration of educational technologies with their practices.